2015
DOI: 10.5301/tj.5000361
|View full text |Cite
|
Sign up to set email alerts
|

Very Elderly (>80 Years), Frail Patients with Muscle-invasive Bladder Cancer and Comorbidities: Is Curative Irradiation Feasible?

Abstract: Our results demonstrate safety and feasibility of curative radiation therapy in very elderly and frail patients with bladder cancer using 3D conformal radiation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Despite the limited size of our sample, sarcopenic and non-sarcopenic patients responded to RT in a similar way, and no significant correlations emerged between SMI and OS, CSS, 90-day mortality and RTtoxicity. In addition, patients' comorbidities expressed according to the CCI score did not influence the OS outcomes though presenting a significant correlation with the experienced toxicity level, in agreement with the results of Santacaterina et al and in contradiction with the studies by Mayr et al and Boorjian et al (4,19,27). Conversely, as only a small number of patients underwent chemotherapy with different regimens in terms of way of administration, time of delivery and pharmacological agents chosen, it is not possible to state how and how much its addition to RT influenced our outcomes.…”
Section: Discussionsupporting
confidence: 77%
“…Despite the limited size of our sample, sarcopenic and non-sarcopenic patients responded to RT in a similar way, and no significant correlations emerged between SMI and OS, CSS, 90-day mortality and RTtoxicity. In addition, patients' comorbidities expressed according to the CCI score did not influence the OS outcomes though presenting a significant correlation with the experienced toxicity level, in agreement with the results of Santacaterina et al and in contradiction with the studies by Mayr et al and Boorjian et al (4,19,27). Conversely, as only a small number of patients underwent chemotherapy with different regimens in terms of way of administration, time of delivery and pharmacological agents chosen, it is not possible to state how and how much its addition to RT influenced our outcomes.…”
Section: Discussionsupporting
confidence: 77%
“…In the case of bladder cancer, the small intestine exists in the head side of the bladder, and efficient dose for curative radiotherapy often can be prescribed by means of filling bladder. For this reason, there are not a few reports of curative radiotherapy for bladder cancer, even in very elderly patients with comorbidities [ 4 ]. However, in the case of UTCC, the small intestine exists closely around the ureter attached with kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Curative conformal RT alone has resulted to be a valid therapeutic approach also in muscle invasive bladder cancer (MIBC) older patients defined unfit both for surgery and systemic therapy due to their comorbidities. Indeed, several studies reported [ 24 , 25 , 26 ] the feasibility and the efficacy of RT alone with acceptable gastrointestinal (GI) or genitourinary (GU) side effects [ 27 ].…”
Section: Planning and Treatment In Older Patientsmentioning
confidence: 99%
“…[ 24 ] 2002 R 45 75 (70–85) MIBC CFRT 56-64/28-32 63 Median OS 21.5 months G1/2 GI and/or GU toxicity (100) - Santacaterina et al. [ 25 ] 2015 R 27 84.5 (81–91) MIBC CFRT 60-64/30-32 17.5 Mean OS 23.5 months G1/2 GI and/or GU toxicity (55.5) G1/2 GI and/or GU toxicity (11) Wujanto et al. [ 27 ] 2019 R 45 77 (65–95) MIBC CFRT 50–69.8/30-40 31 Median OS 56 months G1/2 GI and/or GU toxicity (89) G3 cystitis (2.2) Soyfer et al.…”
Section: Planning and Treatment In Older Patientsmentioning
confidence: 99%